"Who Is at 'Fault?'" The Media and the Stories of Induced Seismicity. Issue 1 (February 2017) - Fisk, Jonathan M.; Davis, Charles; Cole, Benjamin
Abstract : Media attention to earthquake risks linked to the underground injection of produced waters from oil and gas fracking operations has increased over the past few years. However, little scholarly attention has been devoted to newspaper coverage of events and state policy actions that are associated with "induced seismicity." A key concern addressed in this article is whether newspaper coverage is largely unrestrained or is restricted by other factors. Is coverage by differing newspapers influenced by frames emphasizing the economic importance of oil and gas production within the state? We conclude that the answer is "yes" based on information gleaned from content analyses of newspapers in Ohio, Oklahoma, and Texas from 2009 through 2014. Related Articles: Delshad, Ashlie B. 2013 . "Telling Stories: Exogenous Influences on Media, Presidential, and Congressional Framing of Biofuels ."Politics & Policy 41 (2 ):213 ‐240 .http://onlinelibrary.wiley.com/doi/10.1111/polp.12009/abstract Lavery, Lesley. 2013 . "Gender Bias in the Media? An Examination of Local Television News Coverage of Male and Female House Candidates ."Politics & Policy 41 (6 ): 877-910.http://onlinelibrary.wiley.com/doi/10.1111/polp.12051/full Johnson, Tyler. 2012 . "Equality, Morality, and the Impact of Media Framing: Explaining Opposition to Same‐Sex Marriage and Civil Unions ."Politics & Policy 40 (6 ):1053 ‐1080 .http://onlinelibrary.wiley.com/doi/10.1111/j.1747-1346.2012.00398.x/full Related Media: USGS. n.d. "Induced Earthquakes."https://earthquake.usgs.gov/research/induced/ Earthquakes in Oklahoma.2016 . "FAQs."https://earthquakes.ok.gov/faqs/ Oklahoma's Rise in Quakes Linked to Man‐Made Causes.2016 . CBSNews.com .http://www.cbsnews.com/news/60-minutes-oklahoma-rise-in-quakes-linked-to-man-made-causes/